Pemberantasan korupsi : melalui hukum pidana nasional dan internasional - Hamzah, Andi; Indonesia; Indonesia (Jakarta : RajaGrafindo Persada, 2005)
Combating corrupt practices in Indonesia according to Indonesian and international criminal laws.
Revision of the author's thesis (doctoral)--Universitas Hasanuddin, 1982
Includes the texts of: Undang-Undang Tentang Perubahan atas Undang-Undang nomor 31 tahun 1999 Tentang Pemberantasan Tindak Pidana Korupsi, Undang-Undang Tentang Komisi Pemberantasan Tindak Pidana Korupsi, United Nations Convention against Corruption (2003).
Includes bibliographical references (p. 253-262) and index.
In Indonesian, and one text in English
Keywords: Corruption -- Law and legislation -- Indonesia; Corruption -- Indonesia -- Prevention; Political corruption -- Law and legislation -- Indonesia; Political corruption -- Indonesia -- Prevention